Environmental Marine Geoscience 4. Georgia Basin: Seabed Features and Marine Geohazards - Barrie, J.; Hill, Philip; Conway, Kim; Iwanowska, Kashka; Picard, Kim (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2005)
SUMMARY A multibeam bathymetric swath-mapping program of the Strait of Georgia has provided a 5-m resolution map of the seabed. Numerous geological features of the basin, some of which are considered geohazards, are clearly defined. During the Olympia interglacial period most of the basin was filled with sediment and then subsequently excavated during the Fraser Glaciation, except for a group of isolated banks; the southern basin was partially filled by the pro-grading Fraser River Delta during the Holocene. Marine geohazards that exist in this seismically active region include, slope stability features, active faults, gas pockmarks, and large migrating sedimentary bedforms. Other features, such as sponge reefs, have developed because of the glacial history and dynamic oceanography of the basin and provide unique and critical habitats to marine species.